Estradiol-dependent and independent effects of FGF21 in obese female mice - T. V. Jakovleva; A. Yu. Kazantseva; A. D. Dubinina; N. Yu. Balybina; K. O. Baranov; E. N. Makarova; N. M. Bazhan (Вавиловский журнал генетики и селекции)
The f ibroblast growth factor 21 (FGF21) synthesized in the liver, acting as a hormone, increases insulin sensitivity and energy expenditure. FGF21 administration has potent benef icial effects on obesity and diabetes in humans, cynomolgus monkey, and rodents. The therapeutic effects of FGF21 have been studied mainly in males. They are not always manifested in females, and they are accompanied by sex-specif ic activation of gene expression in tissues. We have suggested that one of the causes of sexual dimorphism in response to FGF21 is the effect of estradiol (E2). Currently, it is not known how estradiol modif ies the pharmacological effects of FGF21. The objective of this study was to study the inf luence of FGF21 on metabolic characteristics, food intake, and the expression of carbohydrate and fat metabolism genes in the liver, adipose tissue, and hypothalamus in female mice with alimentary obesity and low (ovariectomy) or high (ovariectomy + E2) blood estradiol level. In ovariectomized (OVX) females, the development of obesity was induced by the consumption of a high sweet-fat diet (standard chow, lard, and cookies) for 8 weeks. We investigated the effects of FGF21 on body weight, blood levels, food preferences and gene expression in tissues when FGF21 was administered separately or in combination with E2 for 13 days. In OVX obese females, FGF21, regardless of E2-treatment, did not affect body weight, and adipose tissue weight, or glucose tolerance but increased the consumption of standard chow, reduced blood glucose levels, and suppressed its own expression in the liver (Fgf21), as well as the expression of the G6pc and Acacα genes. This study is the f irst to show the modif ication of FGF21 effects by estradiol: inhibition of FGF21-inf luence on the expression of Irs2 and Pklr in the liver and potentiation of the FGF21-stimulated expression of Lepr and Klb in the hypothalamus. In addition, when administered together with estradiol, FGF21 exerted an inhibitory effect on the expression of Cpt1α in subcutaneous white adipose tissue (scWAT), whereas no stimulating FGF21 effects on the expression of Insr and Acacβ in scWAT or inhibitory FGF21 effect on the plasma insulin level were observed. The results suggest that the absence of FGF21 effects on body and adipose tissue weights in OVX obese females and its benef icial effect on food intake and blood glucose levels are not associated with the action of estradiol. However, estradiol affects the transcriptional effects of FGF21 in the liver, white adipose tissue, and hypothalamus, which may underlie sex differences in the FGF21 effect on the expression of metabolic genes and, possibly, in pharmacological FGF21 effects.